Hesbollah Kuranji at the Front Padang Area (1945-1948) - Revi Handayani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
AbstractThis paper examines the struggle of the militant ranks Hezbollah at the Front Padang Area. Most of the literature written only talks about the role of regular soldiers (official soldiers recruited by the government) who often fight in the front lines, even though the activation of the militias also contributed the most significant contribution to the struggle at that time physical revolution. The Hezbollah written in this article is Hezbollah in the Padang Region, especially those who are members of the Padang City Hezbollah, who are aware of the existing situation and conditions, so they are persistently trying to reclaim their homeland from the colonial powers of the Allies and the Dutch who want to re-establish their power. The research method in this paper is the historical method, which critically examines and analyzes records and relics. The research steps consist of four stages: Heuristics, Criticism, Interpretation and Historiography. In collecting data and research materials, both historical actors and witnesses were used, apart from using literature and documentary studies and interviews with sources. The result of this research is that the struggle of the Hezbollah Army (Lasykar) of Padang City is based on the intention of